2021
DOI: 10.1097/sla.0000000000005312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Duration of Smoking Cessation Prior to Surgical Treatment of Non-small Cell Lung Cancer

Abstract: Objective: To define the relationship between the duration of smoking cessation and postoperative complications for patients with lung cancer undergoing surgical treatment. Background: Smoking increases the risk of postoperative morbidity and mortality in patients with lung cancer undergoing surgical treatment. Although smoking cessation before surgery can mitigate these risks, the ideal duration of preoperative smoking cessation remains unclear. Methods: Using a uniquely compiled Veterans Health Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Despite the relatively high smoking prevalence among surgical patients (14.7%), guideline-concordant treatment rates were very low, with only 12.7% receiving pharmacotherapy and 31.7% receiving any treatment 3 . This is concerning given the well-established relationship between smoking and multiple adverse outcomes following surgery 2,9 . Further, while our study assessed any treatment, some guidelines suggest that both behavioral support and pharmacotherapy should be the standard of care 4 ; if so, then the guideline-concordant treatment rates in our study are much lower (<5%).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively high smoking prevalence among surgical patients (14.7%), guideline-concordant treatment rates were very low, with only 12.7% receiving pharmacotherapy and 31.7% receiving any treatment 3 . This is concerning given the well-established relationship between smoking and multiple adverse outcomes following surgery 2,9 . Further, while our study assessed any treatment, some guidelines suggest that both behavioral support and pharmacotherapy should be the standard of care 4 ; if so, then the guideline-concordant treatment rates in our study are much lower (<5%).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we performed RCS functions to investigate nonlinear associations between BMI and the incidence of breast cancer. As the RCS function enables a continuous variable to be analyzed without categorization, information and statistical power are not lost in RCS analysis, unlike general regression analysis, which requires categorization of continuous variables such as BMI [13][14][15][16][17]. In this study, we used 4 points (18.5, 22.0, 25.0, and 30.0 kg/m 2 ) as the knots in the cubic splines to allow for nonlinear dose-response effects of continuous BMI measurement, similar to that in previous studies [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For wound healing, the risk was lower in smokers who quit more than 3–4 weeks before surgery than in current smokers. In a recent study by Heiden et al, in patients with early-stage NSCLC, those who were able to stop smoking at least 3 weeks before surgery had reduced postoperative mortality and complications [ 21 ]. For each extra week of abstinence before surgery, the authors found an 8.1% reduction rate in the odds of major complication or mortality cessation (OR for every additional week, 0.919; 95% CI 0.850–0.993, p = 0.03) [ 21 ].…”
Section: Optimal Timing Of Smoking Cessation Prior To Surgerymentioning
confidence: 99%